(untitled) (Annals of Medical Research, 2021)
Aim: Characterized by hypopigmented cutaneous lesions, vitiligo is a chronic dermatological disease with psychosocial effects. The goal of our study is to search alexithymia, anxiety, and depression levels in vitiligo patients.Materials and Methods: In total, 50 vitiligo patients aged over 18 years and 70 healthy control subjects compatible with age and gender were evaluated. All participants filled in the questionnaires of the Toronto Alexithymia Scale (TAS-20), Beck Anxiety inventory (BAI), and Beck Depression inventory (BDI).Results: In vitiligo patients, depression and anxiety levels were meaningful higher than the controls (p = 0.009, p = 0.000, respectively), but there was no meaningful difference between alexithymia scores (p = 0.103). There was no correlation between psychiatric scale scores and disease duration, age, gender, and education levels in vitiligo patients. A positive correlation was determined between alexithymia levels and anxiety and depression levels in vitiligo.Conclusion: In this study, anxiety and depression levels were found to be high in patients with vitiligo. According to the results of our study, vitiligo should not only be evaluated dermatologically but also psychologically. In this way, we think that patients’ compliance with treatment and treatment success will increase.